Maternal Health Behaviors and Infant Health Outcomes Among Arab American and Non-Hispanic White Mothers in Massachusetts, 2012-2016. (September 2020) - Abuelezam, Nadia N.; Cuevas, Adolfo G.; Galea, Sandro; Hawkins, Summer Sherburne
Objectives: The health profile of Arab American mothers and infants may differ from that of non–Arab American mothers and infants in the United States as a result of social stigma experienced in the historical and current sociopolitical climate. The objective of our study was to compare maternal health behaviors, maternal health outcomes, and infant health outcomes of Arab American mothers and non-Hispanic white mothers in Massachusetts and to assess the role of nativity as an effect modifier. Methods: Using data from Massachusetts birth certificates (2012-2016), we conducted adjusted logistic and linear regression models for maternal health behaviors, maternal health outcomes, and infant health outcomes. We used Arab ethnicity as the exposure of interest and nativity as an effect modifier. Results: Arab American mothers had higher odds than non-Hispanic white mothers of initiating breastfeeding (adjusted odds ratio [aOR] = 2.61; 95% CI, 2.39-2.86), giving birth to small-for-gestational-age infants (aOR = 1.28; 95% CI, 1.18-1.39), and having gestational diabetes (aOR = 1.31; 95% CI, 1.20-1.44). Among Arab American mothers, non–US-born mothers had higher odds than US-born mothers of having gestational diabetes (aOR = 1.80; 95% CI, 1.33-2.44) and lower odds of initiating prenatal care in the first trimester (aOR = 0.41; 95% CI, 0.33-0.50). In linear regression models, infants born to non–US-born Arab American mothers weighed 42.1 g (95% CI, −75.8 to −8.4 g) less than infants born to US-born Arab American mothers. Conclusion: Although Arab American mothers engage in positive health behaviors, non–US-born mothers had poorer maternal health outcomes and access to prenatal care than US-born mothers, suggesting the need for targeted interventions for non–US-born Arab American mothers.